Promoting Effect of Gd2O3 in Pt-Gd2O3/C Electrocatalyst for Methanol Oxidation Reaction. Issue 3 (1st March 2022) - Sharma, Shuchi; Shanmugam, Ramasamy; Sahoo, Malaya K.; Rao, G. Ranga
Abstract : Metal oxides have been used as supports and promoters to enhance the electrocatalytic activity of Pt/C for methanol oxidation reaction (MOR). In this work, Gd2 O3 prepared by simple precipitation method (Gd2 O3 (PC)) and polymer-assisted method (Gd2 O3 (PL)) is examined as support for Pt/C. The Gd2 O3 samples are characterized by FTIR, HR-SEM, and PXRD. The ease of surface oxygen exchange and formation of surface –OH groups are better in the case of Gd2 O3 (PC) for MOR activity. The microwave-assisted polyol reflux method is used to prepare Pt-Gd2 O3 (PC)/C and Pt-Gd2 O3 (PL)/C) electrocatalysts. Electrocatalysts are characterized by XPS, ICP, TEM, PXRD, and examined by cyclic voltammetry (CV), CO stripping experiments, chronopotentiometry (CP), and chronoamperometry (CA) in acidic media. The MOR activity of Pt-Gd2 O3 (PC)/C is found to be 2.8 times higher than commercial Pt/C with good anti-poisoning activity. This result is further corroborated by the first principle calculations which show that there is significant electron transfer from Pt/Gd2 O3 to adsorbed CO. This electron transfer reduces the Gibbs free energy for CO adsorption and decreases the CO poisoning. The overall benefit of Gd2 O3 is to increase the performance of Pt electrocatalyst for methanol oxidation.